The Development of Reading Comprehension from Using Context Clues on Facebook of High School Students in Bangkok - Pandito (Krongbuaban), Phra Bandit (Mahachula Academic Journal, 2021)
The purposes of this quasi-experimental study were: (1) to study high school students’ reading comprehension using context clues on Facebook before and after the experiment, (2) to compare high school students’ reading comprehension using context clues on Facebook and traditional teaching method before and after the experiment, (3) to analyze high school students’ reading comprehension using context clues on Facebook, in academic year 2020. The key informants were 34 students, which were divided by purposive sampling method into two groups: control group used the traditional teaching method with context clues consisting of 17 students and the experimental group used context clues on Facebook consisting of 17 students. The research instruments were used for data collection: students’attitude questionnaires, reading comprehension (pretest and posttest). The data were analyzed by means, standard deviation and t-test. The results showed that : - The average score after the treatment was 13.17 ( =13.17), S.D. = .97). 12.23 ( =12.23), S.D. = 1.55). The average difference of the scores before and after the treatment was 5.24 and 3.29 and the t-test statistic value was 7.56 and 11.4 The differences in post-test was higher significant difference at 0.05 levels. 3. High school students’ reading comprehension using context clues on Facebook at a high level with the arithmetic mean ( =4.27), (S.D. = 0.20).